ANALISIS KADAR ALKOHOL PADA OBAT BATUK SIRUP ANAK: VALIDASI METODE HALAL PRODUK - Shesanthi Citrariana; Puspa Dwi Pratiwi; Yahya Febrianto (Jurnal Farmasi Medica/Pharmacy Medical Journal (PMJ), 2024)
The global halal market, including halal food and beverage products, is expected to continue to grow widely. Halal food and drinks according to Islamic law have the criteria of being free from alcoholic, intoxicating and dangerous drinks as well as food additives containing derivatives of these drinks. There are many medicinal preparations circulating on the market that contain alcohol, one of which is cough medicine. This study aims to validate the method and measure alcohol levels in children's cough medicine taken randomly on the market. The method used is GC (Gas Chromatography) with validation determination in the form of linearity tests, system suitability tests, accuracy, LOD and LOQ calculations. The results of this study show that the linearity is R = 0.998. In the system suitability test, the chromatographic N value was >1000, HETP <0.3, and R >1.5. The accuracy obtained is in the range 81.13% - 123.57%. The LOD value is 0.1106% and LOQ is 0.3352%. As well as alcohol residue found in cough medicine samples of 0.075%. From these results it can be concluded that the GC (Gas Chromatography) method used has good validity and the residual alcohol content in children's cough medicine preparations meets the BPOM and MUI halal requirements. Keywords: Gas Cromatography, validation, halal, medicine